2018
DOI: 10.1590/1980-57642018dn12-010009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of education on performance of adults on the Clock Drawing Test

Abstract: The Clock Drawing Test (CDT) is an important instrument for screening individuals suspected of having cognitive impairment. Objective: To determine the influence of education on the performance of healthy adults on the CDT. Methods: A total of 121 drawings by healthy adults without neurological complaints or impairments were analysed. Participants were stratified by educational level into 4 subgroups: 27 illiterate adults, 34 individuals with 1-4 years of formal education, 30 with 5-11 years, and 30 adults wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
1
10
0
3
Order By: Relevance
“…These studies have tended to find greater homogeneity in cognitive behavior among individuals with 8 or more years of education. 1 , 3 , 4 , 13 The same effect can be observed on language tests, although tasks that are highly dependent on the lexical buffer, such as oral and written naming and verbal fluency tests, appear to differ. 2 , 12 …”
mentioning
confidence: 72%
See 2 more Smart Citations
“…These studies have tended to find greater homogeneity in cognitive behavior among individuals with 8 or more years of education. 1 , 3 , 4 , 13 The same effect can be observed on language tests, although tasks that are highly dependent on the lexical buffer, such as oral and written naming and verbal fluency tests, appear to differ. 2 , 12 …”
mentioning
confidence: 72%
“…Although many studies demonstrate the influence of education on cognitive development, 1 - 4 , 8 , 9 , 12 , 13 the impact of low education on the various cognitive functions appears to differ. In a previous study assessing several cognitive domains of individuals with 0-22 years of formal education, the authors noted that the education effect was non-linear: significant differences were evident between groups with 0-3 versus 10-22 years of formal education, whereas the same was not observed between groups with 4-9 and 10-22 years of formal education.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was also noted that the combination of VF and BNT has better sensitivity and specificity in the educated group, while that was better with VF/CDT in the illiterate group. In a study by de Noronha et al to determine the influence of education on the performance of healthy adults on the CDT found that CDT was not strongly influenced by education in its application, except for illiterate individuals, who attained statistically significant lower scores [14]. Accordingly, it can be used clinically for screening cognitive deficits irrespective of education.…”
Section: Discussionmentioning
confidence: 99%
“…The education level is highly recognized as a factor that impacts in tasks that are used to assess not only the language, but also other cognitive functions, such as memory, attention, executive function, and even nonverbal cognitive tasks (Ardila, et al, 2010;Noronha, Barreto, & Ortiz, 2018). The discursive production is regarded as a complex task that requires the integration of several linguistic cognitive skills, such as memory, idea selection, organization, planning, and naming (Alexander, 2006;Rogalski et al, 2010;Andreetta, Cantagallo, & Marini, 2012;Wills, Capilouto, & Wright, 2012;Cannizzaro & Coelho, 2013).…”
Section: Introductionmentioning
confidence: 99%